O jogo poético nas Sete Cabeças de Eucanaã Ferraz: beleza e monstruosidade - Silva, Gerson Lourenço da (2012)
This research analyzes some poems of the work Seven-headed Monster and Other Fantastic Beings (Bicho de Sete Cabeças e Outros Seres Fantásticos), by the Brazilian poet Eucanaã Ferraz. The main question is to verify the presence of game features in the infantile poetry, taking into consideration the postulates defended by Huizinga, especially with regard to the role of the game in the poetic process. Games, as well as poetry, involve the faculty of invention, creation, competition, imagination, tension and seriousness. The poem is built by elements that attract and repel each other, and it is in these inconstancies that the beauty of poetry is: the tension and distension. We sought to understand how the process of construction and deconstruction of the monstrosity occurs in some eucanaanian poems through the poetic game. The theoretical support of the research has relied primarily on studies of poetic language and its specificities, as well as critical studies about children's literature in authors such as: Nelly Novaes Coelho, Decio Pignatari, Octavio Paz, Ezra Pound, Paul Valery and others. For the purpose of contextualization, of the infantile poetry in Brazil, a brief historical view was prepared from its inception to present day. The eighteen selected poems were divided and analyzed into two groups, organized from two nuclear axes: one that turns to the binary-various movement inscribed by the conjugation, in the poems, of two beings into one and, another that focuses on the reconstruction of monsters, giants and legendary creatures, commonly associated to horror, through softness and lightness. Ferraz shows, in his poetic creation, especially in the book Seven-headed Monster and Other Fantastic Beings, a series of legendary, mythological and folkloric references of the universal culture, making the distant near, the strange familiar, the heavy light, rudeness beautiful, harmonizing beings or things of different universes. It is the antithetical game of the binary-various , in a hybrid dimension of attraction and repulsion, which becomes present in the analyzed poems